Neuroeducação e práticas pedagógicas dos professores de escolas públicas das séries finais do ensino fundamental em ensino de Ciências - Santiago Júnior, Clorijava de Oliveira (2016)
In this research, linked Line of research tem cognition Curriculum and pedagogical an understand practices as two professors who work years early we do Primary Education Sciences, having as basis Neuroeducation gives you grounds. The emergence in Neuroeducação it gave the using intercession enters Psychology, Neuroscience and Education series. Try de uma emerging field and that helps to modify or human functional structures limiting in learning and perfect headquarters operations intelligence of using your brain mapping, allowing at maximum expression of its potential. Barnacle is that as important pedagogical Practices are more tools to turn effective and appropriate as requirements of each student. That, this is happening or teacher must direct its activities and evaluation to objectives catch up mutual, with a level diversified curriculum, differentiated pedagogical Practices. I main authors underpin this research were Piaget (1967); Gardner (1994); Houzel (2002); Lundy-Ekman (2008); Relvas (2010); Cosenza and Guerra (2007); Lent (2013) Krasilchik (1987); (Heber Maia (2014) we chose a qualitative method obtaining dice. The sample found 16 teachers Public Elementary School State Network submitted voluntarily to form um, contain eight Questions. About here, questions sought to reflect on Knowledge the two non-respect teachers to use the teaching techniques fundamentals in Neuroeducation. Concluded that Neuroeducation should be present pedagogical Practices at the, because seeks to instrumentalize or teacher using application practices. Was modernity developed to turn to education more enjoyable and overcome disabilities as learning